(untitled) (The Planet, 2025)
Background: Community health education is a cornerstone of preventive public health, yet evidence on its impact in low-resource settings remains limited. This study assessed the effectiveness of structured health education interventions on knowledge, behavior change, and community health outcomes in Bangladesh. Methods & Materials: A cross-sectional analytical study was conducted among 200 participants, of whom 122 received structured health education covering hygiene, nutrition, physical activity, substance use, and preventive care. Data were collected via structured questionnaires assessing Health Knowledge Scores (0–100), Behavior Change Scores (0–10), health facility visits, and self-reported health. Statistical analyses included chi-square tests and regression modeling. Results: Participants showed high levels of knowledge (56.5% scored ≥71) and behavioral change (61.5% scored ≥7). Key outcomes included improved hygiene (83.6%), better diet (72.1%), increased physical activity (67.2%), and reduced substance use (47.5%). Regular health facility use (76.2%) and self-rated good/excellent health (82.8%) were also reported. Gender and age significantly influenced outcomes. Conclusion: Structured community health education significantly improves knowledge, behaviors, and perceived health status. Tailored, demographic-sensitive approaches can enhance program impact and uptake.